EXPRESSION OF ANTIVIRAL GENE ON TIGER SHRIMP Penaeus monodon AT DIFFERENT TISSUE AND BODY SIZE - Andi Parenrengi; Andi Tenriulo; Samuel Lante (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2012)
The role of tiger shrimp defense against invading pathogen on molecular level such antiviral gene expression is limited to be reported. Gene expression is a process which codes information of genes that is converted to the protein as a phenotype. Distribution of PmAV antivirus gene, that has been reported as an important gene on non-specific response immune, is needed to be observed to several organs/tissues and size of tiger shrimp. The aim of this study is to determine the distribution of gene antiviral expression at several organ/tissue and size of shrimp. The organs/tissues observed in this study were: gill, hepatopancres, muscle tissue, eyes, heart, stomach, gonad, and intestine. While the size of shrimp consisted of three groups, those are: (A) 10-20 g/ind., (B) 30-40 g/ind., and (C) 60-70 g/ind. Analysis of antiviral gene expression was performed by RNA extraction, followed by the cDNA syntesis, and amplification of gene expression by semi-quantitative PCR. The result of PCR optimation showed the optimal concentration of cDNA and primer was 1 μL and 50 mol, respectively for PCR final volume of 25 μL. Antiviral gene was expressed on the hepatopancreas and stomach in percentage of 50.0% and 16.7%, respectively. While the highest percentage of individual expressing the antiviral gene was observed in the shrimp size of C (66.7%), followed by B (50.0%) and A (16.7%). The result of study implied that the hepatopancreas has importantly involed in tiger shrimp defense mechanism on viral infection.